In-ovo feeding with creatine monohydrate: implications for chicken energy reserves and breast muscle development during the pre-post hatching period - Dayan, Jonathan; Melkman-Zehavi, Tal; Goldman, Noam; Soglia, Francesca; Zampiga, Marco; Petracci, Massimiliano; Sirri, Federico; Braun, Ulrike; Inhuber, Vivienne; Halevy, Orna; Uni, Zehava (Frontiers in Physiology, 2023)
The most dynamic period throughout the lifespan of broiler chickens is the pre-post-hatching period, entailing profound effects on their energy status, survival rate, body weight, and muscle growth. Given the significance of this pivotal period, we evaluated the effect of in-ovo feeding (IOF) with creatine monohydrate on late-term embryos’ and hatchlings' energy reserves and post-hatch breast muscle development. The results demonstrate that IOF with creatine elevates the levels of high-energy-value molecules (creatine and glycogen) in the liver, breast muscle and yolk sac tissues 48 hours post IOF, on embryonic day 19 (P < 0.03). Despite this evidence, using a novel automated image analysis tool on day 14 post-hatch, we found a significantly higher number of myofibers with lower diameter and area in the IOF creatine group compared to the control and IOF NaCl groups (P < 0.004). Gene expression analysis, at hatch, revealed that IOF creatine group had significantly higher expression levels of myogenin (MYOG) and insulin-like growth factor 1 (IGF1), related to differentiation of myogenic cells (P < 0.01), and lower expression of myogenic differentiation protein 1 (MyoD), related to their proliferation (P < 0.04). These results imply a possible effect of IOF with creatine on breast muscle development through differential expression of genes involved in myogenic proliferation and differentiation. The findings provide valuable insights into the potential of pre-hatch enrichment with creatine in modulating post-hatch muscle growth and development.